Solitary osteolytic skull metastasis as the only recurrence of advanced gastric cancer: a case report and literature review. (2nd January 2022) - Cho, Seongmin; Choi, Jae Young; Kim, Jong Yeol; Seo, Kyung Won; Chang, Hee Kyung; Park, Yong-Seok; Kim, Byung Sup
Abstract: Bone metastases from gastric cancer are very rare, and skull metastases develop in only 11.2% among patients who develop bone metastases from gastric cancer. We report a case of solitary osteolytic skull metastasis as the only recurrence of advanced gastric cancer. A 67-year-old man was referred to us with a two-month history of headache and progressive scalp swelling in the left parietal region. A right hemiparesis developed a week before admission. Thirteen months previously, he had undergone radical total gastrectomy with Roux-en-Y reconstruction. Pathological analysis indicated well-differentiated adenocarcinoma of the gastric cardia (stage IIIA: pT3N2M0). Brain magnetic resonance imaging showed a large skull metastasis in the left parietal region (approximately 65 × 54 mm). An extensive search did not reveal any other tumors. Gross total tumor resection was performed, and the biopsy revealed an adenocarcinoma, suggesting metastasis of the gastric cancer.